MEASURING THE EFFECTIVENESS OF DECENTRALIZATION POLICY THROUGH THE COMMUNITY SATISFACTION INDEX: A SURVEY OF PUBLIC PERCEPTION OF THE QUALITY OF BASIC SERVICES IN THE LAUTÉM MUNICIPALITY, TIMOR LESTE - Domingos Loe Soares, Patricia Baliana da Costa, Carolina da Cruz Simeão Fatima Martins, Jaimito Soar (JURNAL PENDIDIKAN IPS, 2026)
The decentralization policy in Timor-Leste, as a post-conflict nation, aims to bring public services closer to the community, improve their quality, and strengthen state legitimacy at the local level. This study presents a comprehensive empirical evaluation of the effectiveness of this policy in the Lautém Municipality by analyzing the level of community satisfaction with three pillars of basic services: education, health, and population administration. Using a quantitative approach with a survey method involving 350 heads of households selected through stratified random sampling, this research adopts a modified SERVQUAL framework. The results show that the overall Community Satisfaction Index (CSI) score is 76.5 out of 100, which falls into the Good category. However, this finding conceals significant disparities among service types, population administration services scored the highest (81.2), reflecting the success of procedure standardization, followed by education (77.8), while health services significantly lagged with the lowest score (70.5), primarily due to issues with medicine availability and facilities. Multiple linear regression analysis identifies that the dimensions of responsiveness (β = 0.35, p < 0.01) and empathy (β = 0.25, p < 0.01) are the strongest predictors of community satisfaction, surpassing physical aspects (tangibles). These results indicate that although decentralization has shown a positive impact, its effectiveness is not yet uniform, and its success heavily depends on the quality of interaction between citizens and officials. A focused improvement in the capacity of local officials and a reformulation of resource allocation strategies, especially in the health sector, are necessary to realize the full potential of the decentralization policy.